Retrospective study of ALK rearrangement and clinicopathological implications in completely resected nonsmall cell lung cancer patients in northern Thailand: Role of screening with D5F3 antibodies - Apichat Tantraworasin (2018)
Background: Anaplastic lymphoma kinase (ALK) gene rearrangement in non-small cell lung cancer (NSCLC) has been intensively studied. The gold standard for ALK detection is FISH, but this is not routinely conducted in clinical practice, so that the IHC method has a role. The aim of this study was to identify the incidence of ALK rearrangement and risk or prognostic factors for ALK positivity using both of IHC and FISH methods. Materials and Methods: From January 2008 to December 2012, 267 completely resected NSCLC patients in Chiang Mai University Hospital were enrolled in this study. Clinical and pathological variables and outcomes of treatment were retrospectively reviewed. IHC and FISH were used to evaluate ALK rearrangement. Sensitivity and specificity of IHC were analyzed. Multivariable analysis was used to identify clinico-pathological correlations with positive results of IHC and clinical outcomes. Results: Twenty-two (8.2%) of 267 specimens were IHC-positive for ALK with intense cytoplasmic staining, whereas only 10 (3.8%) were FISH-positive. Sensitivity, specificity and the positive likelihood ratio with IHC were 80.0%, 94.9%, and 15.8 respectively. Age less than 55 years (RR 4.4, 95%CI 1.78-10.73, p value=0.001) and presence of visceral pleural invasion (VPI) (RR 2.9, 95%CI 1.21-6.78, p value =0.017) were identified as risk factors for ALK rearrangement with FISH. There were no statistically significant differences in other clinical and pathological variables. ALK rearrangement was not a prognostic factor for tumor recurrence or overall survival. Conclusions: The incidences of ALK positivity in completely resected NSCLCs in northern Thailand were 8.2% by IHC and 3.8% by FISH. IHC with mouse monoclonal, Ventana D5F3 antibody can be used as a screening tool before FISH method because of high specificity and high positive likelihood ratio. Age less than 55 years and VPI are risk factors for ALK positivity.